Protocol for a scoping review of existing policies on the prevention and control of obesity across countries in Africa - Adom, Theodosia (BMJ Open, 2017)
INTRODUCTION: The obesity epidemic is a public health challenge for all, including low-income countries. The behavioural patterns known to contribute to the rise in obesity prevalence occur in an environmental context which is not conducive for healthy choices. A policy approach to obesity prevention constitutes a form of public intervention in that it extends beyond individuals to influence entire populations and is a mechanism for creating healthier environments. Little is known about obesity prevention policies in Africa. This scoping review seeks to examine the nature, extent and range of policies covering obesity prevention in Africa in order to assess how they align with international efforts in creating less obesogenic environments. This will help identify gaps in the approaches that are adopted in Africa. METHODS AND ANALYSIS: Using the Arksey and O'Malley's scoping methodological framework as a guide, a comprehensive search of MEDLINE (PubMed), MEDLINE (EbscoHost) CINAHL (EbscoHost), Academic Search Complete (EbscoHost) and ISI Web of Science (Science Citation Index) databases will be carried out for peer reviewed journal articles related to obesity prevention policies using the African search filter. A grey literature search for policy documents and reports will also be conducted. There will be no language and date restrictions. Eligible policy documents and reports will be obtained and screened using the inclusion criteria. Data will be extracted and results analysed using descriptive numerical summary analysis and qualitative thematic analysis. ETHICS AND DISSEMINATION: No primary data will be collected since all data that will be presented in this review are based on published articles and publicly available documents, and therefore ethics committee approval is not a requirement. The findings of this systematic review will be presented at workshops and conferences; and will be submitted for publication in peer-reviewed journal. This will also form a chapter of a PhD thesis.